2018
DOI: 10.1175/mwr-d-17-0198.1
|View full text |Cite
|
Sign up to set email alerts
|

An Analog Technique to Improve Storm Wind Speed Prediction Using a Dual NWP Model Approach

Abstract: This study presents a new implementation of the analog ensemble method (AnEn) to improve the prediction of wind speed for 146 storms that have impacted the northeast United States in the period 2005–16. The AnEn approach builds an ensemble by using a set of past observations that correspond to the best analogs of numerical weather prediction (NWP). Unlike previous studies, dual-predictor combinations are used to generate AnEn members, which include wind speed, wind direction, and 2-m temperature, simulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 47 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…This type of method is constantly employed for forecasting weather data, such as wind speed, wind direction, temperature, and so on [8]. Basically, numerical weather prediction (NWP) models [9] are used for predicting future data through applying current physical data and topographical information [10]. Dong et al proposed a comprehensive review of NWP models and put forward an effective hybrid model to predict day-ahead wind power [11].…”
Section: B Literature Review 1) Physical Methodsmentioning
confidence: 99%
“…This type of method is constantly employed for forecasting weather data, such as wind speed, wind direction, temperature, and so on [8]. Basically, numerical weather prediction (NWP) models [9] are used for predicting future data through applying current physical data and topographical information [10]. Dong et al proposed a comprehensive review of NWP models and put forward an effective hybrid model to predict day-ahead wind power [11].…”
Section: B Literature Review 1) Physical Methodsmentioning
confidence: 99%
“…The probabilistic forecast itself may have systematic errors, which can be removed by statistical postprocessing, or by an approach like the Analog Ensemble approach, which builds an ensemble by using a set of past observations that correspond to the best analogs of NWP forecasts. This approach has been used to improve the skill of both deterministic and probabilistic forecasting for both wind and solar power (Yang, Astitha, Delle Monache, & Alessandrini, 2018). Recent developments in renewable energy forecasting have focused on probabilistic forecasts and can be divided into two groups: univariate and multivariate probabilistic forecasting.…”
Section: Postprocessing Numerical Weather Predictionsmentioning
confidence: 99%
“…Slingo and Palmer showed that the root mean square error of the ensemble mean anomaly forecast grew from less than 1 to 70 for forecast lead times ranging from hours to decades [30]. Yang et al compared the forecast wind speed for 146 storms based on the Weather Research and Forecasting (WRF) and Integrated Community Limited Area Modeling System models, showing that the RMSE for both models increased from zero hours to 54 forecast hours [31]. Using the gridded Bayesian linear regression to improve the deterministic wind speed prediction with the NCAR's Real-Time Ensemble Forecast System, the authors showed that R-square decreased by 28% and centered root mean square error increased by 38% for lead times ranging from 0 to 48 h [32].…”
Section: Introductionmentioning
confidence: 99%